Connecting Cerebral White Matter Lesions and Hypertensive Target Organ Damage - Cristina Sierra; Alfons López-Soto; Antonio Coca (Journal of Aging Research)
Chronic hypertension leads to concomitant remodeling of the cardiac and vascular systems and various organs, especially the brain, kidney, and retina. The brain is an early target of organ damage due to high blood pressure, which is the major modifiable risk factor for stroke and small vessel disease. Stroke is the second leading cause of death and the number one cause of disability worldwide and over 80% of strokes occur in the elderly. Preclinical hypertensive lesions in most target organs are clearly identified: left ventricular hypertrophy for the heart, microalbuminuria for the kidney, fundus abnormalities for the eye, and intima-media thickness and pulse wave velocity for the vessels. However, early hypertensive brain damage is not fully studied due to difficulties in access and the expense of techniques. After age, hypertension is the most-important risk factor for cerebral white matter lesions, which are an important prognostic factor for stroke, cognitive impairment, dementia, and death. Studies have shown an association between white matter lesions and a number of extracranial systems affected by high BP and also suggest that correct antihypertensive treatment could slow white matter lesions progression. There is strong evidence that cerebral white matter lesions in hypertensive patients should be considered a silent early marker of brain damage.